Analysis of Enterprise Resource Planning System (ERP) in Small and Medium Enterprises (SME) of Malaysian Manufacturing Sectors: Current Status and Practices - Khaleel, Yousef; Riza Sulaiman,; Nazlena Mohamed Ali,; Mohd Syazwan Baharuddin, (Penerbit UKM, 2011)
Small and Medium-sized Enterprise (SME) requires to tap the power of Information Technology (IT) and integrate information system in order to stay competitive and customer oriented. Thus, the Enterprise Resource Planning (ERP) is one solution to integrate information technology infrastructure to meet global competition. This research paper investigates the factors that prevent Malaysian SMEs from fully adopting the ERP system. Through various literatures, this paper will address the degree of factors that gave an impact and provide rating of impact to the SMEs. Quantitative surveys were done in 21 SMEs to understand the actual situation of ERP adoption. The research instrument use was the online survey system. Results from the survey concludes that the on-availability of suitable ERP system the meets the SME business needs is one of the five important factors that prevents the adoption of such system.